Effect of humic acid as a photosensitizer combined with low-energy laser on orthodontic tooth movement in rats - Yang An; Jianmei Zhao; Hang Xu; Li An; Jun Wang; Yang Wu; Qingmei Liu (Elsevier, 2022)
Background/purpose: Humic acid (HA) could promote light conversion reaction, and lasers accelerate orthodontic tooth movement. We investigated the effect of HA, as a photosensitizer, combined with low-energy laser on orthodontic tooth movement in rats. Materials and methods: An orthodontic tooth movement model was established, and the upper left first molar was moved mesially by a nickel-titanium tension spring with a 50-g force. HA was injected into the rats' abdominal cavity (80 mg/kg once daily). The periodontal tissue of the upper left upper first molar on the pressure side was irradiated (50 s once every 2 days) using a semiconductor laser (wavelength, 650 nm; power, 50 mV). Distance moved by the upper left first molar was measured at different time points, and the tissue of the first molar was sectioned and scanned by micro-computed tomography to evaluate the alveolar bone density. Tartrate-resistant acidic phosphatase staining was used to observe the osteoclast number, alveolar bone, and periodontal tissue. Results: HA alone did not significantly affect orthodontic tooth movement, alveolar structure density, or periodontal tissue remodeling (P > 0.05). HA combined with a low-energy laser accelerated orthodontic tooth movement. The number of bone absorption lacunae and osteoclasts on the alveolar bone's pressure side increased significantly (P < 0.05), while the density decreased significantly (P < 0.05); however, no root absorption was observed. Conclusion: HA can improve the conversion rate of low-energy lasers, enhance the low-energy laser effect, and promote orthodontic tooth movement and periodontal tissue reconstruction on the pressure side in rats, without causing root resorption.